Regional Specialization and Geographic Concentration of Economic Sectors in the Visegrád Countries - Ágnes Hegyi-Kéri (Theory, Methodology, Practice, 2013)
As a result of transformational recession, the mono-structural economy has changed in the Visegrád countries. The transformation process is not yet finished. The new economic structure has been shaped by the concentration of sectors by delocalization, central industry and spatial planning. In this paper the aim was to find an answer to the following question: What kind of sector concentrations and specialized processes took place in the Visegrád countries, which included Hungary, Poland, Czech Republic and Slovakia in connection with reindustrialization and deindustrialization during the years 2000-2007? Due to the macrostructure’s spatial concentration, the regions’ specifications, and the (de)polarization processes of the last few years determined the ability to adapt to the economic crisis. The regional specialization and concentration processes of the Visegrád countries will be compared using various kinds of indicators (absolute and relative concentration), and special attention is paid to regional analysis within Hungary. The research questions are: after the political change of regime, where and what type of sector or industry concentration has been established in the examined countries? Is it possible to say that some specialization or concentration is disadvantagous to economic growth? The difference between regional specialization and concentration and the terms related to industrialization are also clarified.